Les ordonnances de dédommagement et de restitution en droit pénal canadien - Gagné, Jacques (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1979)
This paper examines the constitutional law issue raised before the Supreme Court of Canada in the case of R. v. Anne Zelensky and the T. Eaton Co. Ltd. and the Attorney General of Canada, decided on May 1, 1978. Having discussed the judgment of the Manitoba Court of Appeal, the author proceeds to support the majority decision of the Supreme Court, as expressed by the Chief Justice, viz. that the provision for compensation orders in subsection 653(1) of the Criminal Code is intra vires the federal Parliament as part of the sentencing process. The paper then proceeds to draw a comparison between compensation orders under subsection 653(1) and probation orders under paragraph 663(2) e) of the same Code. Differences in the nature of these two classes of orders are brought out. In view of the limited scope for application of subsection 653(1) the author suggests a number of legislative changes. These changes would remove all the constitutional difficulties inherent in the present drafting of the subsection. They would also fashion a more efficient instrument for compensating victims of crime, while preserving the original purpose of rehabilitating the offender.